Implementation Of Curriculum Management Through A Conducive Learning Environment - Muhammad Nasir; Ainul Andy Sudarmoko; Triyo Supriyatno; Bintoro Widodo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Learning environment management as an important aspect in the education system has a major role in facilitating a conducive, systematic, and effective learning process. This study examines and reviews the management of the learning environment in MI Manarul Islam, Malang City. A conducive learning environment influences academic achievement, learners' motivation, and their emotional comfort. Teachers play a key role in establishing a conducive learning atmosphere by using creative learning approaches, managing the classroom effectively, and creating positive interpersonal relationships with learners. This research focuses on the aspects that have a major influence on the success of learning management, which includes the physical and non-physical aspects. In addition, this research will also review the role of teachers in creating a conducive learning environment. This research adopts a qualitative approach using the case study method. This research adopts a qualitative approach using the case study method. Researchers made direct observations in Class VI MI Manarul Islam, to observe the learning environment, facilities, and interactions that occur in it. The results of this study indicate that the management of the learning environment at MI Manarul Islam has been done well. The aspects studied include physical and non-physical aspects. Physical aspects consist of spatial layout, ventilation, lighting, organization of equipment and learning media, as well as cleanliness and tidiness. Meanwhile, non-physical aspects include learning motivation, teacher teaching style, teacher attitude, teacher communication skills, and classroom climate.